Voice Therapy According to the Rehabilitation Treatment Specification System: Expert Consensus Ingredients and Targets - Van Stan, Jarrad H.; Whyte, John; Duffy, Joseph R.; Barkmeier-Kraemer, Julie; Doyle, Patricia; Gherson, Shirley; Kelchner, Lisa; Muise, Jason; Petty, Brian; Roy, Nelson; Stemple, Joseph; Thibeault, Susan; et al. (American journal of speech-language pathology, 2021)
Purpose Clinical trials have demonstrated that standardized voice treatment programs are effective for some patients, but identifying the unique individual treatment ingredients specifically responsible for observed improvements remains elusive. To address this problem, the authors used a taxonomy of voice therapy, the Rehabilitation Treatment Specification System (RTSS), and a Delphi process to develop the RTSS-Voice (expert consensus categories of measurable and unique voice treatment ingredients and targets). Method Initial targets and ingredients were derived from a taxonomy of voice therapy. Through six Delphi Rounds, 10 vocal rehabilitation experts rated the measurability and uniqueness of individual treatment targets and ingredients. After each round, revisions (guided by the experts' feedback) were finalized among a primary reader (a voice therapy expert) and two external readers (rehabilitation experts outside the field of voice). Consensus was established when the label and definition of an ingredient or target reached a supramajority threshold (≥ 8 of 10 expert agreement). Results Thirty-five target and 19 ingredient categories were agreed to be measurable, unique, and accurate reflections of the rules and terminology of the RTSS. Operational definitions for each category included differences in the way ingredients are delivered and the way individual targets are modified by those ingredients. Conclusions The consensus labels and operationalized ingredients and targets making up the RTSS-Voice have potential to improve voice therapy research, practice, and education/training. The methods used to develop these lists may be useful for other speech, language, and hearing treatment specifications. Supplemental Material https://doi.org/10.23641/asha.15243357.